Concise Three-Step Strategy for the Synthesis of 2-Benzoxepin-3(1H)-ones - Madhurima, Hazra; Krishna, Jonnada; Satyanarayana, Gedu (Synthesis, 2015)
A short and efficient method was developed for the synthesis of 2-benzoxepin-3(1H)-ones. The synthetic sequence comprises of initial intermolecular Heck coupling, followed by reduction of the carbonyl functionality of the Heck product and finally base-induced intramolecular condensation. Notably, the final condensation may proceed by an interesting oxy-Michael addition, cycloreversion via double bond isomerization and intramolecular condensation.
Keywords: palladium catalysis; Heck coupling; reduction; condensation; benzoxepinones